Do longer articles gather more citations? Article length and scholarly impact among top biomedical journals - Lyu, Peng‐hui; Wolfram, Dietmar (Proceedings of the Association for Information Science and Technology, 2018)
ABSTRACT Publications represent the most tangible products of research and scholarly communication. Growing pressures placed on researchers to increase their publication counts may encourage them to publish shorter papers, so that more publications may be generated from the same project and program. Is this the case? Furthermore, do shorter papers garner the same impact as longer papers as measured by the citations received? This research examines the relationship between article length and citations received by articles published in three prominent top biomedical research journals over the lifetime of the journals. The study reveals that instead of getting shorter, articles in these journals are getting longer over time. Longer articles in these journals, on average, attract more citations, and are therefore considered more impactful.